2018
DOI: 10.1016/j.scienta.2018.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and kinetic parameters of the uptake of nitrogen forms in clonal peach rootstocks

Abstract: Peach (Prunus persica L.) rootstock cultivars are typically selected for scion compatibility, ease of propagation, vigor, development, flowering season, yield, low need for cold temperatures, resistance to diseases, effects on the physical-chemical characteristics of the fruit, plant longevity and adaptation to adverse edaphoclimatic conditions. However, kinetic parameters related to nutrient uptake efficiency are usually not considered, such as those of nitrate (NO 3 −) and ammonium (NH 4 +). N is the nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…Following the acclimation period, plants were induced to the depletion of internal nutrient reserves in a 0.01 mol L −1 CaSO 4 solution (Vetec Chemistry, Xerem, Brazil), which provided only Ca and S needed to preserve the cell membrane integrity and maintain the electrochemical potential 10 . Plants were separated into two groups composed of five plants for each treatment (‘Okinawa’ rootstock with and without scion graft).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the acclimation period, plants were induced to the depletion of internal nutrient reserves in a 0.01 mol L −1 CaSO 4 solution (Vetec Chemistry, Xerem, Brazil), which provided only Ca and S needed to preserve the cell membrane integrity and maintain the electrochemical potential 10 . Plants were separated into two groups composed of five plants for each treatment (‘Okinawa’ rootstock with and without scion graft).…”
Section: Methodsmentioning
confidence: 99%
“…Plants with a higher need for N can also be selected according to kinetic parameters, 8,9 but most will probably demand nitrogen fertilizer applications with a higher frequency and/or in more significant quantities throughout the crop cycle. Paula et al 10 . and collaborators reported that, for some peach rootstocks, such as the Tsukuba 1, there was a higher uptake rate and NO 3 − affinity when compared with Aldrighi and Clone 15, indicating that distinct peach rootstocks may have different kinetic parameters, which alters N uptake efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…For example, N is an important element for crop growth. The forms of N element in the growing environment of crops are NH 4 + and NO 3 − [ 113 ]. Much research has been conducted on these two ASSISEs [ 29 , 46 , 114 ].…”
Section: Prospection Of Crop Detection Applicationsmentioning
confidence: 99%
“…Peach tree, the third largest deciduous fruit tree in China, is a type of NO 3 − -N-loving plant, absorbs NO 3 − -N as the main nitrogen source, and has low- and high-affinity transport systems to absorb NO 3 − -N fertilizer [ 23 ]. Due to the lack of understanding of the nitrogen absorption and metabolism in peach trees, the phenomenon of excessive application of nitrogen fertilizers in peach production is relatively common, which not only leads to the imbalance of phosphorus, potassium and micronutrients, but also increases the workload of tree management, reduces fruit quality, and even causes physical diseases.…”
Section: Introductionmentioning
confidence: 99%